Interaction between innate immunity and Ro52-induced antibody causes Sjögren's syndrome-like disorder in mice. Issue 3 (5th February 2015) - Szczerba, Barbara M; Kaplonek, Paulina; Wolska, Nina; Podsiadlowska, Anna; Rybakowska, Paulina D; Dey, Paromita; Rasmussen, Astrid; Grundahl, Kiely; Hefner, Kimberly S; Stone, Donald U; Young, Stephen; Lewis, David M; et al.
Abstract : Objectives: Autoantibodies reactive with Ro52 are often found in sera of patients with Sjögren's syndrome (SS). This study was undertaken to investigate the role of Ro52-induced immune responses in pathogenesis of SS. Methods: New Zealand Mixed (NZM) 2758 mice were immunised with Ro52 in alum adjuvant. Control mice were immunised either with maltose-binding protein or injected with alum alone. Mice were monitored for anti-Ro52 antibody, sialoadenitis and pilocarpine-induced salivation. Antibody binding to salivary gland (SG) cells was analysed in vivo and in vitro by immunofluorescence. Sera from immunised mice were passively transferred into untreated or alum injected NZM2758 mice. Results: By day 30 post-immunisation, Ro52 immunised mice generated immunoprecipitating anti-Ro52 antibodies and they had the maximum drop in saliva production. Both Ro52 immunised and control mice showed evidence of mild sialoadenitis. However, only Ro52 immunised mice had antibody deposition in their SG. Passive transfer of Ro52-immune sera induced SG dysfunction in recipient mice, only if the recipients were primed with alum. In vitro, antibodies from Ro52-immune sera were internalised by a SG cell line and this uptake was inhibited by cytochalasin D treatment. Conclusions: Our data show for the first time that antibodies induced by Ro52 are capable of inducing SG dysfunction, and that this phenomenon is dependent on the activation of innate immunity. The mouse model described in this study implies that autoantibody deposition in the SG might be an important step in the induction of xerostomia and pathogenesis of SS.